Empowering at-risk youth in and through vocational education : a comparative view of the Baltic countries and Norway - Tutlys, Vidmantas [Herausgeber]; Tikkanen, Tarja [Herausgeber]; Ümarik, Meril [Herausgeber]; Sloka, Biruta [Herausgeber] (Springer, 2025)
"This book presents insights on the resiliency strategies of at-risk vocational education and training (VET) students in the field of learning, employment and social integration, in the Baltic countries and Norway. It investigates the ways in which vocational education and training (VET) can enhance the social inclusion of young people at-risk, both in terms of combating school dropout rates, and promoting transitions between various (social) learning contexts, such as school-work transition. Book presents the findings of the analysis of available statistical data disclosing the capacities and potential of the VET systems and providers to empower vulnerable learners in the project partner countries. In the context of VET, this book examines the situations of at-risk young people as they experience, and understand themselves, in it, and explores innovative solutions to address their challenges in collaboration between themselves, their teachers, and other community actors and stakeholders. Finally, it analyses and discusses the innovative pedagogical interventions used in empowering at-risk VET students as implemented in the research project 'EmpowerVET', on the basis of the Educational Learning Lab model developed by researchers from the University of Tallinn School of Educational Sciences." (Publisher, BIBB-Doku)
Keywords: P 1.7 Benachteiligte; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; 370; Benachteiligter Jugendlicher; Benachteiligtenförderung; Berufsausbildung; Soziale Integration; Internationaler Vergleich; Estland; Lettland; Litauen; Norwegen